Synergistic interactions of locust bean gum with whey proteins: Effect on physicochemical and microstructural properties of whey protein-based films - Silva, K. S. [UNESP]; Mauro, M. A. [UNESP]; Gonçalves, M. P.; Rocha, C. M.R. (Elsevier, 2016)
Locust bean gum synergistic interactions with whey proteins are widely described in terms of functional properties. The aim of this work is to assess how these interactions affect whey protein-based film properties. Blended films were manufactured using whey protein isolate (WPI), four different concentrations levels of locust bean gum (LBG) and two different thermal treatments. A rheological study was performed to assess interaction between WPI and LBG. The influence of glycerol on WPI/LBG interactions was also verified. Barrier, mechanical, and optical properties, as well as microstructure, solubility and moisture sorption behavior of films were evaluated. The results show that interaction between WPI and LBG and more severe heat treatments provide stronger, more flexible and less soluble films with lower permeability to carbon dioxide and oxygen and lower transparency. These findings suggest that the addition of locust bean gum to WPI can be used to tune the properties of WPI-based edible films to meet specific food packaging and edible coating needs.
Keywords: Biopolymer interactions; Edible films; Film properties; Locust bean gum; Whey protein isolate